An N-heterocyclic carbene based MOF catalyst for Sonogashira cross-coupling reaction; Catalysis Science and Technology; Vol. 6, iss. 7 - Ezugwu Ch. I. Chizoba; Mousavi B. Bibimaryam; Asrafa M. A.; Mehta A.; Vardhan H. Harsh; Verpoort F. V. K. Frensis Valter Kornelius (2016, 2016)
Title screen